Relationship between Untreated Dental Caries and Weight and Height of 6- to 12-Year-Old Primary School Children in Bangladesh. (10th April 2013) - Mishu, Masuma Pervin; Hobdell, Martin; Khan, Mahfujul Haq; Hubbard, Richard M.; Sabbah, Wael
Abstract : Background . Children in low-income developing countries are likely to suffer from undergrowth. Dental caries is another common problem in these countries. Aim . To examine the association between untreated dental caries in primary and permanent teeth with age-adjusted height and weight among 6–12-year-old children in Bangladesh. Design . Social, behavioural, and clinical data were collected from 1699 children in nine different randomly selected primary schools in socially deprived areas of Bangladesh. The associations of age-adjusted weight and height and being underweight with dental caries were examined adjusting for sex, area of residence, socioeconomic position, skipping meals, tooth cleaning, and doctor visits. Results . 26% of the children were underweight and 55% had untreated dental caries. Children with at least one decayed tooth were significantly underweight with odds ratios 1.6 (95% CI 1.1, 2.3) and 1.5 (95% CI 1.1, 2.0) for 6–8-years and 9–12-year-old children, respectively, in the adjusted model. The number of decayed teeth was inversely and significantly associated with the standardized age-adjusted weight. Conclusions . The findings highlight the association between untreated dental caries and being underweight in primary school children in socially deprived areas in low-income developing countries and emphasize the need to integrate oral and general health policies with social policies.